Solid-state Deposition of Bulk Metallic Glass and High-entropy Alloy via Cold Spray - Fan, Ningsong (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2024)
Metallic glasses (MGs) and high-entropy alloys (HEAs) are both emerging multi-component alloys with unique microstructures and extraordinary properties. Cold spray, as a burgeoning solid-state material deposition process, plays an active role in manufacturing high-performance coatings and restoring damaged metal parts and has been moved into solid-state additive manufacturing in recent years, which provides an alternative to allow the fabrication of MGs and HEAs. The low processing temperature involved in cold spray helps to minimize metallurgical defects, such as phase transformation, oxidation, and crystallization (for MGs), in the deposits and retain an original structure as feedstock powder. For MGs, although the study on cold-sprayed BMGs has been carried out in the past two decades, the interparticle bonding mechanism and dynamic evolution of crystallization are both unclear and need further clarification. While for HEAs, the study on microstructure evolution and mechanical properties of cold-sprayed HEAs is quite limited, and systematic research on cold spraying HEA coatings or deposits is imperative to widen their potential application. The equiatomic CoCrFeNi HEA, serving as a basic system in the HEA family, was selected as the research object and fabricated by cold spraying. Considering the high deformation resistance of CoCrFeNi HEA, which may lead to the formation of pores and poor interparticle bonding even under high processing parameters, various strengthening strategies (i.e., post heat-treatment, in-process densification, and microalloying) were carefully combined with the cold spray process to intentionally modify the microstructure and improve the mechanical properties (e.g., tensile properties, compressive properties, and wear resistance) of the cold-sprayed CoCrFeNi HEA. The main research content and results of this study are as follows: Amorphous Zr55Cu30Ni5Al10 bulk metallic glass deposit was produced by cold spray. The bonding mechanism of metallic glass particles was systematically investigated by studying the deformation behavior of individual particles after deposition. In addition, the dynamic evolution mechanism of the amorphous phase into nanocrystal structures at severely deformed interfacial regions during cold spray was also carefully investigated. The results showed that two collective particle bonding mechanisms contributed to the formation of metallic glass deposits, i.e., high-velocity impact induced localized metallurgical bonding at the fringe of the interface and high particle temperature induced viscosity reduction and the resultant annular metallurgical bonding band. Moreover, the different amorphous/nanocrystal structures in cold-sprayed metallic glass deposits, which can represent different evolution stages in the nanocrystallization process, were observed for the first time. The nanocrystallization process can be divided into the following three stages: composition segregation, the formation of ordered 1D and 2D transition structures, and 3D nanocrystals. The CoCrFeNi high-entropy alloy (HEA) was fabricated by cold spray and then post-spray annealed at the temperature range of 500-1000 ?C for 2 hours. By adjusting the annealing temperature, four types of deposits (i.e., as-sprayed, recovered (500 ?C), partially recrystallized (700 ?C), and fully recrystallized (1000 ?C) deposits) were obtained, and their microstructure, compressive and tensile properties were systematically explored. The results showed that the as-sprayed deposit exhibited high compressive yield strength but fractured within the elastic deformation regime in the tensile test. Only recover annealing hardly influenced the microstructure and mechanical properties of the deposits. While recrystallization annealing could trigger enhanced interface diffusion and the resultant metallurgical bonding. The partially recrystallized and fully recrystallized deposits exhibited an excellent combination of compressive strength and ductility. While the fully recrystallized deposit exhibited almost equal tensile and compressive yield strength and the best recovery of tensile ductility. The CoCrFeNi HEA deposits were fabricated using different combinations of particle size ranges and gas parameters. The microstructure evolution, deformation behavior, and mechanical properties of the deposits under different combinations were investigated. The results showed that a combination of a wide particle size range of the feedstock powder and low gas parameters could trigger in-process densification of the deposits. At such conditions, a proportion of the particles (particularly those with large sizes) fail to deposit and rebound after their impact instead. The rebound particles result in accumulative plastic deformation of the deposited particles and further reduction in porosity. With this novel strategy, the detrimental thermal effects encountered in cold spraying using high-temperature processing gas (such as oxidation, nitridation, and phase changes) can be effectively minimized. However, the strategy comes at the expense of the large-sized particles, implying low deposition efficiency. Moreover, the mismatch between the particle size ranges and the gas parameters will lead to the inclusion of less deformed large-sized particles, leading to the formation of large pores and deteriorated mechanical performance. Microalloying strategy was applied to CoCrFeNi HEA feedstock powder, and the CoCrFeNiMox (x=0, 0.2, 0.5, and 1) deposits were fabricated by cold spray to improve the wear resistance of CoCrFeNi deposits. The microstructure evolution, mechanical properties, and tribological properties were systematically investigated. The results showed that Mo0, Mo0.2, and Mo0.5deposits have a face-centered-cubic (FCC) single structure, while Mo1.0 deposits were composed of FCC matrix and hard brittle phases. The doping of Mo element into CoCrFeNi HEA deposits significantly increased the hardness due to the enhanced solid solution strengthening and precipitation strengthening. As a result, the anti-wear properties of Mo-doped CoCrFeNi HEA deposits were gradually improved with the increase in Mo ratios. The Mo1.0 deposit exhibited the lowest specific wear rate of 0.51 ? 10-4 mm3/N?m, which was reduced by 94.9% in comparison to the Mo0 deposit.
APPROVED
Keywords: Additive manufacturing; Bulk metallic glass (BMG); Cold spray; High-entropy alloy (HEA); Plastic deformation; Microstructure; Mechanical properties